In Planta Agrobacterium-Mediated Genetic Transformation In Okra {Abelmoschus Esculentus (L.) Moench} (Applied Biological Research, 2018)
In Planta methods have been developed in several plant species to overcome  the problems associated with their tissue culture-based transformation. In  present study, a method for genetic transformation in okra (Abelmoschus  esculentus) was established using in planta Agrobacterium-mediated genetic  transformation. The embryos of imbibed seeds pricked from meristematic region of plumule were used as explants for transformation. Agrobacterium  tumefaciens strain EHA105 was carrying cry1Ac gene against fruit and  shoot borer, CaMV 35S as promoter and nptII as plant selectable marker  gene. The putative transgenic plants were confirmed by amplifying  transgene through polymerase chain
Keywords: Abelmoschus esculentus; Bacillus thuringiensis; shoot and fruit borer; transgenic okra